Role of JIGSAW method of teaching in improving clinical diagnosis among final year medical students – A prospective observational study - S, Appandraj; V, Sivagamasundari; Varatharajan Sakthivadivel, (Asian Journal of Medical Sciences, 2021)
Background: The Jigsaw method is a form of cooperative learning, in which students are actively involved in the teaching-learning process that improves the long-term retention of acquired knowledge. Aims and Objectives: The objective of this study was to assess the knowledge acquired by students using the Jigsaw learning method in Internal Medicine. Materials and Methods: A prospective observational study was conducted with 100 students. The acute coronary syndrome was taken for 1 h as a didactic lecture, and a pre-test was conducted. The students were divided into five groups and were put for the intervention “Jigsaw.” The pre- and post-test were conducted, and feedback was collected from the students. Paired t-test was used to perform analysis of pre- and post-test. Feedback evaluation was done by a 5-point Liker scale. P<0.05 was considered statistically significant, and the data were analyzed using CoGuide software. Results: The mean pre-test score was 8.44 ± 2.33 ranged (3–14) and the mean post-test score was 11.03 ± 2.07 (ranged 6–15). The difference of 2.39 (95% CI: 2.19–2.59) increase in marks post-test after the Jigsaw method was statistically significant (P<0.001). The satisfaction level was 50–55% on the Likert scale based on the questionnaire given. There was a significant improvement in the post-test scores of the students after Jigsaw. Conclusion: The Jigsaw method improved knowledge in the short-term by engaging students in group work and motivation to learn. Overall response based on the questionnaire about the Jigsaw method was positive.